Modelling pig sector dynamic adjustment to livestock epidemics with stochastic-duration trade disruptions - Niemi, Jarkko K.; Lehtonen, Heikki (Oxford University Press, 2011)
We use a stochastic dynamic programming model to simulate the market implications of alternative foot and mouth disease scenarios in the Finnish pig sector. The model considers the dynamics of animal stock adjustment and price movements when the duration of export disruptions is unknown. Explicit treatment of these issues is crucial in the economic analysis of livestock epidemics, especially if there is a risk of a prolonged export ban. Results suggest that the risk of a prolonged ban increases disease losses considerably. It also increases economic benefits from production adjustments.
Keywords: Ma; Ko; dynaaminen ohjelmointi; hätärokotukset; sika; riskit; eläintaudit; kustannukset; tappiot; suu- ja sorkkatauti; swine; foot and mouth disease; animal diseases; risks; dynamic programming; supply; trade ban